Live Attenuated Measles Virus Vaccine Expressing Helicobacterpylori Heat Shock Protein A - Iankov, Ianko D. (Mol Ther Oncolytics, 2020)
Measles virus (MV) Edmonston derivative strains are attractive vector platforms in vaccine development and oncolytic virotherapy. Helicobacter pylori heat shock protein A (HspA) is a bacterial heat shock chaperone with essential function as a Ni-ion scavenging protein. We generated and characterized the immunogenicity of an attenuated MV strain encoding the HspA transgene (MV-HspA). MV-HspA showed faster replication within 48 h of infection with >10-fold higher titers and faster accumulation of the MV proteins. It also demonstrated a superior tumor-killing effect in vitro against a variety of human solid tumor cell lines, including sarcoma, ovarian and breast cancer. Two intraperitoneal (i.p.) doses of 10(6) 50% tissue culture infectious dose (TCID(50)) MV-HspA significantly improved survival in an ovarian cancer xenograft model: 63.5 days versus 27 days for the control group. The HspA transgene induced a humoral immune response in measles-permissive Ifnarko-CD46Ge transgenic mice. Eight of nine animals developed a long-term anti-HspA antibody response with titers of 1:400 to 1:12,800 without any negative impact on development of protective anti-MV immune memory. MV-HspA triggered an immunogenic cytopathic effect as measured by an HMGB1 assay. The absence of significant elevation of PD-L1 expression indicated that vector-encoded HspA could act as an immunomodulator on the immune check point axis. These data demonstrate that MV-HspA is a potent oncolytic agent and vaccine candidate for clinical translation in cancer treatment and immunoprophylaxis against H. pylori.